BUSINESS MODEL FINANCIALLY VIABLE FOR A RADIO FREQUENCY IDENTIFICATION (RFID) APPLICATION TO HALAL FOOD SYSTEM - Artya Lathifah; Winda Narulidea (Universitas Airlangga, 2017)
Recently, the halal concept has acquired a raising attention. This is as a result of the number of global Muslim population increasing annually. Halal concept has become more popular since Halal food consumers more aware and concern about the integrity of Halal status. Consumers also inquisitive about all the activities involved along the supply chain whether the products that they purchased were truly Halal. In order to accomplish the intent to further develop halal sector, something need to be done to introduce a comprehensive and suitable tracking and tracing technology for the sustainability of the halal product integrity. So, a proper technological framework that can support the entire supply chain of halal product process is needed. This paper discusses a financially viable business model for a Radio Frequency Identification (RFID) application to a halal food traceability system. We use a case study of RFID implementation in the chain of convenience stores from previous research. RFID will give benefits for integrity of the Halal Supply Chain by branding of the trustworthy of the “Halal” itself. For the economic aspect, RFID give advantage not only in responsess to the product availability and customer’s satisfaction but also real time information about demand. Keywords: Financially viable; Halal Supply Chain integrity, RFID, Traceability